Abstract Number ‐ 10: Stroke Patients with Carotid Artery Web Have High RoPE Scores and Low Frequency of PFO - Qasem N Alshaer; Nilushi Karunamuni; Ehizele M Osehobo; Sitara Koneru; David R Landzberg; Alhamza R Al‐Bayati; Fadi Nahab; Raul G Nogueira; Diogo C Haussen (Stroke: Vascular and Interventional Neurology, 2023)
Introduction PFO‐associated stroke is more common in young patients (<60 years) with less vascular risk factors, and with an infarct pattern consistent with embolic phenomena. These features are included in the Risk of Paradoxical Embolization (RoPE) score in which a high score (≥ 7) indicates a high likelihood of a symptomatic PFO. However, carotid artery webs (CaW) have been reported in patients with the same profile in which a PFO might be detected. In this study, we calculated RoPE score for patients with symptomatic CaW related strokes to identify how many of these patients would have been potentially misclassified as having a PFO‐associated stroke. Methods Patients presenting with ESUS and ipsilateral symptomatic CaW were included. Stroke work up was completed including cervicocranial vascular imaging that was reviewed by a neuroradiologist and an interventional neurologist. Shunt study was done with a TTE, TEE, and/or TCD, all with a bubble study. RoPE score of ≥ 7 was considered high. Results A total of 75 patients fulfilled the inclusion criteria of having an ipsilateral symptomatic CaW as the etiology of ESUS with no competing etiologies aside from PFO. The baseline characteristics are described in the table. The rates of vascular risk factors were generally low which is reflected by a high median RoPE score of 7 [IQR 5‐8], with 52% (n = 39) of patients having a score of ≥ 7. Ten patients (13%) had a PFO, of which 3 had high‐risk features. There was no significant difference in median RoPE score between patients with and without PFO (8 [6‐8] vs 6 [5‐8], p = 0.238), nor in the rate of patients with high RoPE score (78% vs 44%, p = 0.06). Recurrence happened in 16% (n = 12) of the patients and was always ipsilateral to the symptomatic CaW. No significant difference was detected in the rates of recurrence between high vs low RoPE scores (20.5% vs 11.1%, p = 0.351). Patients with a PFO had higher rates of recurrence compared to those without a PFO (40%, n = 4 vs 12.3%, n = 8, p = 0.048); however, none of the PFO patients with a recurrent stroke had a high‐risk PFO. A superimposed thrombus was seen on the CaW in 12.2% (n = 9) and was more commonly seen in patients who had recurrence (36%, n = 4 vs 8%, n = 5, p = 0.024). Conclusions Patients with ESUS from a presumably symptomatic CaW‐related stroke have high RoPE scores. The recurrence rates were high in this population and were always ipsilateral to the side of the CaW including in the PFO population. The PFO is likely incidental in this population despite having a high RoPE score. Neurologists should carefully evaluate the cervical vasculature before concluding that a PFO is stroke‐related and committing patients to PFO treatment.